Kesan Program Mengaji Online untuk anak-anak di Kampung Pisang, Sabah Malaysia pada Norma Baharu 2021 - Shafina Binti Amba; Nurazidawati Mohamad Arsad; Rian Vebrianto; Afiq Budiawan; Miftah Audhiha (Anotero Lembaga Scientific Pekanbaru, 2021)
Covid-19 is getting worse and increasing throughout the world, resulting in restrictions on people's movements for activities including carrying out activities in mosques such as tadarus al-Quran every Friday night and recitation of the Koran for children. Our way to reduce the transmission of the corona virus, all activities can only be done from home such as working from home, studying from home, reading the Koran from home and many more. With this background, community service was carried out, namely an online recitation program for children in Kampung Pisang. This service aims to ensure that children can continue to learn to recite the Koran even though they are only online. This is important to continue to carry out because seeing the increasing number of Covid-19 statistics in Malaysia will result in children still not being allowed to do face-to-face recitation of the Koran like before. The method used is Participatory Action Research (PAR) which is held every day except Friday nights at 8:00 pm to 10:00 pm lasts for two hours using the Google Meet application. He involved as many as 9 children from Kampung Pisang, Sabah Malaysia. Data was taken using a satisfaction questionnaire (questionnaire) to determine the success of this program implementation. From the results of the analysis, it is known that this program is very welcome and highly appreciated because there are also those who are willing to carry out such a program. Even though they cannot leave the house, it does not prevent them from getting education and recitation of the Koran. Thus, the results obtained from parents and children who participated in this program strongly agreed with this program and received many positive impressions. For this reason, it is hoped that all stakeholders in Kampung Pisang, especially parents who have to play a role in continuing to support children to take part in this online recitation program so that the world will gradually recover and be able to perform activities of reciting the Koran in mosques face to face.